Rational Design of Antigen Incorporation Into Subunit Vaccine Biomaterials Can Enhance Antigen-Specific Immune Responses - Tsoras, Alexandra N.; Wong, Kong M.; Paravastu, Anant K.; Champion, Julie A. (Frontiers in Immunology, 2020)
Peptide subunit vaccines increase safety by reducing the risk of off-target responses and improving the specificity of the induced adaptive immune response. The immunogenicity of most soluble peptides, however, is often insufficient to produce robust and lasting immunity. Many biomaterials and delivery vehicles have been developed for peptide antigens to improve immune response while maintaining specificity. Peptide nanoclusters (PNCs) are a subunit peptide vaccine material that has shown potential to increase immunogenicity of peptide antigens. PNCs are comprised only of crosslinked peptide antigen and have been synthesized from several peptide antigens as small as 8 amino acids in length. However, as with many peptide vaccine biomaterials, synthesis requires adding residues to the peptide and/or engaging amino acids within the antigen epitope covalently to form a stable material. The impact of antigen modifications made to enable biomaterial incorporation or formation is rarely investigated, since the goal of most studies is to compare the soluble antigen with biomaterial form of antigen. This study investigates PNCs as a platform vaccine biomaterial to evaluate how peptide modification and biomaterial formation with different crosslinking chemistries affect epitope-specific immune cell presentation and activation. Several types of PNCs were synthesized by desolvation from the model peptide epitope SIINFEKL, which is derived from the immunogenic protein ovalbumin. SIINFEKL was altered to include extra residues on each end, strategically chosen to enable multiple conjugation chemistry options for incorporation into PNCs. Several crosslinking methods were used to control which functional groups were used to stabilize the PNCs, as well as the reducibility of the crosslinking. These variations were evaluated for immune responses and biodistribution following in vivo immunization. All modified antigen formulations still induced comparable immune responses when incorporated into PNCs compared to unmodified soluble antigen alone. However, some crosslinking methods led to a significant increase in desirable immune responses while others did not, suggesting that not all PNCs were processed the same. These results help guide future peptide vaccine biomaterial design, including PNCs and a wide variety of conjugated and self-assembled peptide antigen materials, to maximize and tune the desired immune response.